Improvement of concrete carbonation resistance based on a structure modified Layered Double Hydroxides (LDHs): Experiments and mechanism analysis. (10th July 2018) - Shui, Z.H.; Yu, R.; Chen, Y.X.; Duan, P.; Ma, J.T.; Wang, X.P.
Highlights: Three types of Mg-Al-LDHs with different structures are evaluated. The carbonation resistance of concrete with different LDHs are tested. The thermodynamics for structural modification of Mg-Al-LDHs are analyzed. The CO3 2− immobilization abilities of different LDHs are discussed. Carbonation depth prediction model of the concrete with LDHs is discussed. Abstract: This paper addresses a design of a novel concrete with advanced carbonation resistance based on application of a structure modified Layered Double Hydroxides (LDHs) like material, including experiments and mechanism analysis. First of all, according to the concept of structural reconstruction and memory function of LDHs, three types of Mg-Al-LDHs with different structures are produced and evaluated. The thermodynamics analysis demonstrates that the structural modification of Mg-Al-LDHs could be triggered when the heating temperature is higher than 252.8 °C. Then, the carbonation resistance of the concrete with different structure modified Mg-Al-LDHs are tested and compared. The obtained experimental results demonstrate that the carbonation resistance of concrete with calcined Mg-Al-LDHs can be mostly improved, compared to the samples with other structure modified Mg-Al-LDHs. Moreover, several concrete carbonation depth prediction models are employed to evaluate the carbonation resistance of the concrete with structure modified Mg-Al-LDHs. It is proved that, compared to the random model and carbonation mechanism model, the multiple coefficient prediction model is more suitable to be used to predict the carbonation depth for the concrete developed in this study. Additionally, the microstructure development of the concrete with structure modified Mg-Al-LDHs is also discussed in this research.